2022
DOI: 10.1088/1361-6560/ac4c2f
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed low dose-rate radiotherapy: radiobiology and dosimetry

Abstract: Pulsed low dose-rate radiotherapy (PLDR) relies on two radiobiological findings, the hyper-radiosensitivity of tumor cells at small doses and the reduced normal tissue toxicity at low dose rates. This is achieved by delivering the daily radiation dose of 2 Gy in 10 sub-fractions (pulses) with a 3-minute time interval, resulting in an effective low dose rate of 0.067 Gy/minute. In vitro cell studies and in vivo animal experiments demonstrated the therapeutic potential of PLDR treatments and provided useful prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…It was suggested that for malignancies that exhibit lowdose HSR, delivering therapy in a pulsed fashion by dividing the total dose into a number of pulses that are separated by a fixed time interval in which the dose per pulse is below the transition dose of about 0.5Gy could yield an increase in both TCP and normal tissue sparing. However, the effect of the time interval or the effective dose rate was not investigated and the current delivery schedule was chosen for clinical practicality [6]. The low-dose HRS effect may diminish as the total dose accumulates without sufficient time intervals between the pulses, resulting in the eventual accumulation of sufficient damage to induce repair and radiation resistance [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that for malignancies that exhibit lowdose HSR, delivering therapy in a pulsed fashion by dividing the total dose into a number of pulses that are separated by a fixed time interval in which the dose per pulse is below the transition dose of about 0.5Gy could yield an increase in both TCP and normal tissue sparing. However, the effect of the time interval or the effective dose rate was not investigated and the current delivery schedule was chosen for clinical practicality [6]. The low-dose HRS effect may diminish as the total dose accumulates without sufficient time intervals between the pulses, resulting in the eventual accumulation of sufficient damage to induce repair and radiation resistance [12].…”
Section: Discussionmentioning
confidence: 99%
“…PLDR can also prove to be a viable treatment modality against tumors proximal to previously treated healthy tissues which might be near or at its tolerance of received radiation dose. A detailed review of the radiobiology and dosimetric requirements for the implementation of PLDR clinically has been presented by Ma [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of a PRDR program for VMAT can be challenged by machine deliverability. Ideally, the meter rate for a PRDR plan would be adjusted to ensure 6.67 cGy/min to the mean target dose per Ma et al 5 In Elekta systems like the Infinity series, equipped with the Integrity control system, meter rates are continuously variable enabling the meter rate to be programmed to achieve a dose rate adjusted beam. To address this issue, we have developed an alternative approach that enables subfraction-based VMAT delivery at higher meter rates.…”
Section: Planning Methodologymentioning
confidence: 99%
“…Pulsed low-dose-rate radiotherapy (pLDR) is a commonly used reirradiation technique for recurrent high-grade gliomas, but its upfront use with concurrent TMZ is currently under investigation ( 10 – 13 ). While other salvage therapies for recurrent high-grade glioma exist, including stereotactic radiosurgery, conformal external beam radiation, and brachytherapy, pLDR delivers radiation in subfractions at specific time intervals, taking advantage of the hyper-radiosensitivity of proliferating tumor cells to low doses of radiation, as well as the reduced toxicity to normal brain tissue ( 12 , 14 ). Currently, there is limited data on the radiographic response to pLDR.…”
Section: Introductionmentioning
confidence: 99%